PENERAPAN MEDIA PEMBELAJARAN INTERAKTIF ISLAMI PADA MATA PELAJARAN AKIDAH AKHLAK KELAS IV MADRASAH IBTIDAIYAH DARUL HUDA LEUWIPAPAN KADUBUNGBANG CIMANUK(Analisis Deskriptif Kualitatif pada Pembelajaran Akidah Akhlak Kelas IV di MI Darul Huda Leuwipapan Kadubungbang Cimanuk) - Novita Dewi Novita Dewi; Ahmad Hidayat; Asep Budi (Lembaga Sepercenter, 2026)
This study aims to identify, examine, and analyze the form, implementation, and implications/impact of the use of Islamic interactive learning media in the subject of Akidah Akhlak at MIS Darul Huda Leuwipapan. The research problems in this study are: 1) What is the form of Islamic interactive learning media in the subject of Akidah Akhlak at MI Darul Huda Leuwipapan, 2) How is the implementation of Islamic interactive learning media in the subject of Akidah Akhlak at MI Darul Huda Leuwipapan, 3) What are the impacts/implications of the use of Islamic interactive learning media in the subject of Akidah Akhlak at MI Darul Huda Leuwipapan. The research method used in this study is a qualitative method with a descriptive research design. This research was conducted at MIS Darul Huda Leuwipapan in 2026, with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of Islamic interactive learning media in the subject of Akidah Akhlak at MIS Darul Huda Leuwipapan has been carried out quite well and has provided a positive contribution to the learning process. The forms of media used include Islamic learning videos, audio-visual media, and interactive materials adapted to the characteristics of students. The media is implemented during classroom learning activities by utilizing available facilities so that students become more active, focused, and able to understand the material more easily. The impact is seen in the improvement of students’ understanding of Akidah Akhlak materials, increased learning motivation, and the formation of better moral attitudes and behavior in daily life. However, there are still several challenges such as limited facilities and infrastructure, differences in students’ understanding levels, and limited learning time.